2011
DOI: 10.1007/s00246-011-9962-3
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Parents and Children Where Children Have Been Supported with a Ventricular Assist Device as a Bridge to Heart Transplantation

Abstract: There is little information to assist in understanding the experience endured by parents and children where children have been supported with a ventricular assist device (VAD) as a bridge to heart transplantation. Consequently, the aims of this study were to gain an understanding of children's and parents' experience where children have been supported with a VAD as a bridge to heart transplantation and to use this information to improve the Royal Children's Hospital (RCH) VAD program. This study employed a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…In a small study assessing levels of depression of parents whose children were on a VAD, half of mothers were moderately depressed . In a qualitative study, Gilmore and Newall identified that there is a lack of information to prepare families and children for the anticipated course of treatment on VAD support . Given the inevitable small sample sizes in both of these studies, it is difficult to draw meaningful conclusions from these data, but the emerging literature presents a concerning picture for pediatric patients and their families and emphasizes the need for focused psychosocial interventions for this unique population.…”
Section: Implications For the Familymentioning
confidence: 99%
“…In a small study assessing levels of depression of parents whose children were on a VAD, half of mothers were moderately depressed . In a qualitative study, Gilmore and Newall identified that there is a lack of information to prepare families and children for the anticipated course of treatment on VAD support . Given the inevitable small sample sizes in both of these studies, it is difficult to draw meaningful conclusions from these data, but the emerging literature presents a concerning picture for pediatric patients and their families and emphasizes the need for focused psychosocial interventions for this unique population.…”
Section: Implications For the Familymentioning
confidence: 99%
“…Even experienced health care professionals who work in VAD programs may lack understanding of the needs of children who require VADs and of the problems families experience who support them (Gilmore & Newall, 2011). Children and their families may be left feeling grossly unprepared for the reality of VAD implantation (Gilmore & Newall, 2011). Therefore, a pediatric perspective is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Still, it is not clear from the available literature what particular challenges pediatric patients with VADs face because overall, the experience of sending children home on these devices has been limited . Even experienced healthcare professionals who work in VAD Programs may lack understanding of the needs of children who require VADs and the problems of families who support them …”
Section: Introductionmentioning
confidence: 99%